An experimental investigation on interfering VIVs of double and triple unequal-diameter flexible cylinders in tandem. (July 2022) - Zhao, Bing; Fu, Shixiao; Zhang, Mengmeng; Ren, Haojie; Xu, Liangbin; Xie, Wenhui; Jia, Lusheng
Abstract: Many unequal-diameter risers have been widely applied to satisfy different operational requirements in ocean oil and gas drilling engineering, and adjacent tandem risers can undergo complex vibration responses and even collisions under ocean flow conditions. To investigate the wake interference responses for multiple risers in tandem configuration, an experiment of double and triple unequal-diameter flexible cylinders was conducted under uniform flow with Reynolds numbers Re ranging from 2832 to 11, 328 for the larger cylinder and from 1805 to 7220 for the smaller cylinder. The two cylinders were 8 m in length with aspect ratios equal to 282.49 and 443.21, respectively, and the corresponding diameter ratio was 0.64. Two different tandem configurations were arranged with a large cylinder upstream and downstream, and the wall spacing between adjacent cylinders was fixed at 4 D, where D is the diameter of small cylinders. Fiber Bragg grating strain sensors were used to measure both in-line (IL) and cross-flow (CF) strain responses. The modal superposition method was applied to reconstruct displacement responses based on measured strains, and drag forces were further inversely identified from the mean IL displacements. Equivalent wake velocities were calculated from drag force reductions. The results show that the downstream large cylinder in a triple-cylinder system endures a stronger wake interference effect than that in a double-cylinder system. Wake interference can decrease the dominant mode of downstream cylinders and increase the vibration amplitudes due to the reduction in the local wake velocity. In addition, a downstream cylinder undergoing wake-induced vibrations has the same dominant frequency in the CF and IL directions, and its CF frequency is identical to that of the upstream cylinder. Highlights: An experiment of double and triple unequal-diameter flexible cylinders in tandem was conducted, with entire models immersed vertically in water. In addition, the large and small cylinders were 8 m in length with aspect ratios equal to 282.49 and 443.21, respectively, and the corresponding diameter ratio was 0.64. Compared to a double-cylinder system, the downstream large cylinder in a triple-cylinder system endures a stronger wake interference effect from the two upstream small cylinders. Wake interference can decrease the downstream cylinders' dominant mode orders and increase their vibration amplitudes compared to a single cylinder, which results from the reduction of local wake velocity. Upstream cylinders undergo classic VIV responses with a frequency ratio f IL /f CF of approximately 2.0, while the downstream cylinders may experience WIV responses with f IL /f CF equal to 1.0. In addition, the strong vortex shedding from an upstream cylinder can cause downstream SCs to vibrate at the same CF frequency as the upstream cylinder.